Finite Element Analysis of Beam to Column Bolted Connection - A Review - Al-Fakih, K.; Chin, Siew Choo; Doh, Shu Ing (Informatics Publishing Limited, 2017)
Objectives: This paper contains the review of studies performed on the behavior of steel beam-to-column connections by using finite element analysis computer package known as “Abaqus, Ansys, etc” from the theoretical and practical points of view. The objective of this article is providing the foundation for the design and analysis faster and more economical and securing the required strength for the connection steel. Methods/Statistical Analysis: Nearly seventy-one academic and popular research/literature in the field of steel connections had been studied in which an overview of recent events has made the construction of the system viable in the infrastructure. Findings: Linear analysis of connection behavior is very complicated since there is no immediate solution for it. All the results of the accounts of the design connections cannot be verified only through lab tests which consume a lot of time, money and effort. Therefore, the availability of simulation programs can overcome these problems. This article will be of value to anyone seeking better understanding in the area of steel beam-to-column connections behavior. Application/ Improvements: Review study presented in this paper can be used as reference for future investigation especially in the member strength and development of the design approach for steel beam-to-column connections with simulation models.